A statistical quality control study on Fuller O'Brien Paint Co. - Agbay, Arnel; Limgenco, Margaret Marie H.; Tampani, Miles B. (Diliman, Quezon City College of Engineering, 2002)
The company under study, Fuller O'Brien Paint Co., Inc. is a 45 year old company under Wise Holdings, Inc. and is one of the biggest producers of paint and surface chemicals in the country. The focus product of the study is Maxicoat paint which composes 17 percent of the company's total sales. Using various tools, four major problems (which caused 80 percent of the company's problems) were identified and concentrated on. These four trouble areas are unmatched color, low hiding ability, incorrect viscosity, and slow drying time. These four problems appeared both in the FMECA and the problem analysis as critical points. To better understand these problems, three properties were studied, namely, density, viscosity and fineness of grind, since variation in these properties cause the four problems mentioned. From the constructed control charts, previous data confirmed that the process was out of control and non-random. Adjustments were then made in order to create in-control charts from which the process capability ratios were calculated. The process capability ratios showed that the process is only capable of manufacturing within the density specification limits. Production is not capable in terms of the fineness of grind and viscosity specifications. In order to address these problems, recommended steps towards improvement were made and grouped according the four (4) M's, man, machine, material and management. The proponents recommend that administration improve working conditions and implement incentive schemes to reduce human error, that they adopt in-house testing methods to ensure raw material quality, and that they follow a regular machine maintenance plan in order to ensure that machines are always working at full capacity.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Fuller O'Brain Paint Co; Paint industry and trade; Quality control